An Effective and Safe Enkephalin Analog for Antinociception - K. K. DurgaRao Viswanadham; Roland Böttger; Lukas Hohenwarter; Anne Nguyen; Elham Rouhollahi; Alexander Smith; Yi-Hsuan Tsai; Yuan-Yu Chang; Christopher Llynard Ortiz; Lee-Wei Yang; Liliana Jimenez; Siyuan Li; et al. (Pharmaceutics, 2021)
Opioids account for 69,000 overdose deaths per annum worldwide and cause serious side effects. Safer analgesics are urgently needed. The endogenous opioid peptide Leu-Enkephalin (Leu-ENK) is ineffective when introduced peripherally due to poor stability and limited membrane permeability. We developed a focused library of Leu-ENK analogs containing small hydrophobic modifications. N-pivaloyl analog KK-103 showed the highest binding affinity to the delta opioid receptor (68% relative to Leu-ENK) and an extended plasma half-life of 37 h. In the murine hot-plate model, subcutaneous KK-103 showed 10-fold improved anticonception (142%MPE·h) compared to Leu-ENK (14%MPE·h). In the formalin model, KK-103 reduced the licking and biting time to ~50% relative to the vehicle group. KK-103 was shown to act through the opioid receptors in the central nervous system. In contrast to morphine, KK-103 was longer-lasting and did not induce breathing depression, physical dependence, and tolerance, showing potential as a safe and effective analgesic.